1996
DOI: 10.1088/0957-4484/7/2/002
|View full text |Cite
|
Sign up to set email alerts
|

Selective area oxidation of with an ambient scanning tunneling microscope

Abstract: A scanning tunneling microscope tip has been used to selectively write oxidation patterns on a thin Si 3 N 4 film on p + silicon. After etching the patterns in hydrofluoric acid, trenches are observed, consistent with silicon consumption in the oxidation process. The patterns in the nitride film could be transferred to the underlying silicon with an ammonium fluoride etch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, there are few reports in the literature to address this subject. In 1996, Day and Allee 19 reported the possibility of local oxidation on silicon nitride using the tungsten tip of a scanning tunneling microscope ͑STM͒. Very recently, we have successfully proved the conversion of Si 3 N 4 to SiO x with a conductiveprobe AFM.…”
Section: Introductionmentioning
confidence: 90%
“…However, there are few reports in the literature to address this subject. In 1996, Day and Allee 19 reported the possibility of local oxidation on silicon nitride using the tungsten tip of a scanning tunneling microscope ͑STM͒. Very recently, we have successfully proved the conversion of Si 3 N 4 to SiO x with a conductiveprobe AFM.…”
Section: Introductionmentioning
confidence: 90%
“…As is well known, the conventional silicon nitride removal mechanism involves two steps, 17,23 the first and the rate-determining step is the hydrolysis of the silicon nitride at the surface to an oxide 11,15,16 and the second step is the removal of this oxide during polishing. It appears then that Ce 3+ ions, when present in the dispersion, facilitate the conversion of a thin layer of the nitride surface to some form of silicon oxynitride via the following overall reaction, as shown schematically in Figure 13.…”
Section: Proposed Mechanism For Silicon Nitride and Silicon Dioxide R...mentioning
confidence: 99%
“…9,10 Interestingly, however, room temperature electrochemical oxidation of thin nitride films to SiOx has been reported. The early work of Day and Allee 11 showed that low pressure chemical-vapor-deposited (LPCVD) SiN can be oxidized to SiOx using the tungsten tip of an STM operated at a voltage of 10 V and a current of 1 nA. This was followed by a report by Chien et al 12 about the local oxidation of LPCVD silicon nitride films, deposited on conductive substrates, using an AFM at a bias voltage of 10 V with initial oxide formation rates of ∼ 30,000 nm/s but lasting for only ∼10 μs.…”
mentioning
confidence: 99%